2018
DOI: 10.1007/s12603-017-0993-1
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and Musculoskeletal-Functional Outcomes in Community-Dwelling Older People: A Systematic Review and Meta-Analysis

Abstract: A Mediterranean diet is protective of frailty and functional disability, but not of sarcopenia. More longitudinal studies are needed to understand the relationship between a Mediterranean diet and sarcopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 74 publications
1
50
0
1
Order By: Relevance
“…We are aware of only a few studies [40e42; and reviewed in 43,44] that used a 'whole diet' approach to investigate the risk of sarcopenia in adults aged !55, and none in the very old. This limits the opportunity for direct comparisons of our findings with those from other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware of only a few studies [40e42; and reviewed in 43,44] that used a 'whole diet' approach to investigate the risk of sarcopenia in adults aged !55, and none in the very old. This limits the opportunity for direct comparisons of our findings with those from other studies.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have utilised these methods to investigate associations between DPs and sarcopenia (e.g. [40e42], reviewed in [43,44])d the Mediterranean DP has been the most common approach and none of the studies has been conducted in the very old.…”
Section: Introductionmentioning
confidence: 99%
“…Although there was a lack of longitudinal studies, the findings suggested a relationship between healthier diets and better physical function. Two recent systematic reviews investigated the relationship between adherence to a Mediterranean diet and musculoskeletal–functional outcomes; one focused on musculoskeletal health (including bone and muscle outcomes, specifically sarcopenia incidence or combined outcomes) in all ages [ 20 ], while the other investigated the association between a Mediterranean diet and frailty, functional disability and sarcopenia in older people [ 21 ]. The review findings indicate growing evidence of benefits of greater adherence to a Mediterranean diet, although they conclude that further research is needed to understand the relationship between a Mediterranean diet and sarcopenia and musculoskeletal health.…”
Section: Discussionmentioning
confidence: 99%
“…However, much of this evidence is cross-sectional. A recent systematic review on the relationship between diet quality and successful ageing [ 19 ] concluded that with regards to physical function, there were too few longitudinal studies to draw firm conclusions, although there is growing evidence of benefits of greater adherence to a Mediterranean diet [ 20 , 21 ]. To the best of our knowledge no reviews have collated studies, using different definitions of diet quality, to examine effects on sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses of observational studies reveal that high adherence to the Mediterranean diet is associated with a significantly reduced risk of frailty and functional disability [170,171]. Although data are limited in patients with diabetes, some reports indicated that adherence to the Mediterranean diet was associated with decreases in both the prevalence [172] and incidence [173] of frailty in older patients.…”
Section: Mediterranean Diet and Healthy Dietmentioning
confidence: 99%